Research on the Interaction Design of Online Learning Platforms for University Students Based on a User's Mental Model - Jiang, Yujie; Ma, Quandang; Zhang, Lizhou; Ma, Shihui (2023 IEEE 12th International Conference on Educational and Information Technology (ICEIT), 2023)
Based on a user's mental model, the interaction (HCI) design strategy of online learning platforms for university students is explored to provide a theoretical basis for designing and developing online learning platforms. Through the theoretical overview, this study analyses the significance of the involvement of mental models in the interaction design of online learning platforms. A user's mental model for the interaction design of online learning platforms for university students is integrated. Through the quantitative and qualitative analysis of the questionnaire, the current problems and needs of university students in the interactive experience of online learning platforms are summarized. Combining a user's mental model and the questionnaire data, this study proposes an interaction design strategy for university students' online learning platform based on the mental model from three dimensions: the visual, the behavioral, and the reflective dimensions. It is hoped that it will meet the learning needs of university students in the online learning platform， and optimize their online learning experience.